Multicenter Study Differentiated Thyroid Carcinoma (MSDS) - Biermann, M.; Pixberg, M. K.; Schuck, A.; Heinecke, A.; Köpcke, W.; Schmid, K. W.; Dralle, H.; Willich, N.; Schober, O.; the MSDS group (Nuklearmedizin - NuclearMedicine, 2003)
Aim: The Multicenter Study Differentiated Thyroid Carcinoma (MSDS) is an ongoing study in Germany, Austria, and Switzerland on the clinical benefit of adjuvant external beam radiotherapy (RTx) for locally invasive differentiated thyroid carcinoma (DTC) in TNM stages pT4 pN0/1/x M0/x (5th ed. 1997). Methods: MSDS was designed as a prospective randomized trial. Patients receive thyroidectomy, radioiodine therapy (RIT) to ablate the thyroid remnant, and TSH-suppressive L-thyroxine therapy with or without RTx after documented elimination of cervical iodine-131 uptake (http://msdsstudie.uni-muenster.de). Results: 311 patients were enrolled between January 2000 and March 2003. 279 patients met the trial’s inclusion criteria. 45 consented to randomization, of whom 17 were randomized into treatment arm A (RTx) and 18 into arm B (no RTx).Advised by the trial’s independent Data Monitoring and Safety Committee, the MSDS steering committee decided to terminate randomization in April 2003 and continue MSDS as a prospective cohort study. 23 of the 234 patients in the observation arm of the trial were prescribed RTx by their physicians. Thus, 14% of the trial cohort were randomized or assigned to receive RTx (intention-to-treat analysis). In contrast, at least 44% of all patients with pT4 papillary DTC in Germany in the nationwide PCES study underwent RTx in 1996 (p <0.001, χ2-test). Conclusions: Acceptance of external beam RTx as a treatment modality for DTC has receded to a degree that accrual of a sufficient number of patients for a randomized trial has been impossible. Observation of the trial cohort is continued in order to assess clinical event rates with and without RTx and chronic RTx toxicity.
Keywords: Thyroid carcinoma; radiotherapy; randomized trial; radio-iodine; thyroidectomy